(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Strokal V. P. Professional and practical training of students in the structure of environmental education. This study illustrates phases of forming professional-practical study of the future Bachelor students – environmentalists. Main roles of the practical study in the environmental education have been established and discussed.